EFFICACY OF SEVERAL BIOINSECTICIDES ON MORTALITY OF THE PEST Clauges glaculalis ON PULAI PLANTS (Alstonia Angustiloba Miq.) IN THE LABORATORY - Aluyah, Cik; Asmaliyah, Asmaliyah; Sari, Fitri Windra (Universitas Muhammadiyah Palembang, 2023)
Chemical insecticides often have negative impacts if they are not used wisely. The use of bioinsecticides is an alternative to overcome this problem. The aim of this research is to determine the efficacy of several bioinsecticides on the mortality of the insect pest Clauges glaculalis which attacks the pulai plant (Alstonia angustiloba Miq.) on a laboratory scale. The research was carried out at the Laboratory of the Western Indonesian Plantation Forest Research and Development Center (BP2HT IBB) Palembang, using an experimental method with a Completely Randomized Design (RAL) consisting of 11 treatments with 3 replications. The treatments are: C = Cutlass WP microbial insecticide, B = Bactospeine WP microbial insecticide, M = Neem vegetable insecticide, S = Soursop vegetable insecticide, BC = Bactospeine WP+Cutlass WP insecticide, BM = Bactospeine WP+Neem insecticide, BS = insecticide Bactospeine WP+Soursop, MS = Neem+Soursop insecticide, MC = Neem insecticide+Cutlass WP, SC = Soursop insecticide+Cutlass WP, and K = Control (without using insecticide). The results of the study showed that all bioinsecticides tested showed the same efficacy, namely 100% in causing death in Clauges glauculali caterpillars except for the insecticides MS (Neem+Soursop) (67 percent), M (Neem) (67 percent), S (Soursop) (33 percent ), and K= Control (0 percent). Microbial insecticides caused the death of Claugres glauculalis caterpillars more quickly compared to vegetable insecticides, but the death time was even faster for microbial insecticides that were applied in a mixture with vegetable insecticides.